Long Non-coding RNA lnc-GNAT1-1 Suppresses Liver Cancer Progression via Modulation of Epithelial–Mesenchymal Transition - Wang, Jianchu; Wang, Wei; Tang, Qianli; Lu, Libai; Luo, Zongjiang; Li, Wenchuan; Lu, Yuan; Pu, Jian (Frontiers in Genetics, 2020)
Recent studies have investigated the modulatory roles of long non-coding RNAs in the onset and progression of liver cancer. The present study aimed to elucidate the role of lnc-GNAT1-1 in liver cancer development and to explore the underlying mechanisms. Quantitative real-time polymerase chain reaction was performed to measure the expression levels of lnc-GNAT1-1 in cancerous tissues from patients with liver cancer and in liver cancer cell lines. The proliferative ability and apoptotic rates of liver cancer cells were measured using the counting kit-8 (CCK-8), colony formation, and flow cytometry assays. The abilities to invade and migrate were measured using Transwell assays. Epithelial–mesenchymal transition (EMT)-related proteins, E-cadherin, N-cadherin, and vimentin, were measured using western blotting. A nude mouse model was injected with xenografts to evaluate tumor growth in vivo. Downregulation of lnc-GNAT1-1 was observed in cancerous tissues from patients with liver cancer and in liver cancer cell lines, and low expression levels of lnc-GNAT1-1 were related to advanced TNM stage. Lnc-GNAT1-1 knockdown promoted invasion, migration, and proliferation of liver cancer cells and inhibited apoptosis, while lnc-GNAT1-1 upregulation exerted the opposite effects. The expression levels of lnc-GNAT1-1 negatively correlated with in vivo tumor growth in a xenograft nude mouse model. Mechanistic experiments revealed that lnc-GNAT1-1 exerted anti-tumor effects in liver cancer cells by inhibiting EMT. In conclusion, this study suggests that lnc-GNAT1-1 suppresses liver cancer progression by modulating EMT.